Особенности кадрового обеспечения индустриализации в Украине на основе сотрудничества республик (1926 – 1932) - Борбачева, Л.В. (Наука. Релігія. Суспільство, 2013)
Статья посвящена проблемам обеспечения индустриализации квалифицированными кадрами специалистов на основе сотрудничества советских республик. Статья написана на широком архивном материале Украины, Российской Федерации, раскрывает проблемы взаимной помощи советских республик в обеспечении кадрами процесса индустриализации. В статье охарактеризованы формы и методы сотрудничества республик. Стаття присвячена проблемам забезпечення кваліфікованими кадрами фахівців на основі співробітництва радянських республік. Стаття написана на значному архівному матеріалі України, Російської Федерації, розкриває проблеми взаємодопомоги радянських республік у забезпеченні кадрами процесу індустріалізації. У статті подана характеристика форм та методів співробітництва республік. Аrticle is dedicated to the problem of the provision of qualified personnel to industrialization, based on cooperation between Soviet Republics. The article is written on the basis of extensive Ukrainian and Russian archival materials, it reveals the problems of mutual assistance of the Soviet republics to provide personnel to the process of industrialization. The article describes the forms and methods of cooperation between republics. The aim of the study is to examine the experience of cooperation between Soviet republics in the staffing of industrialization in Ukraine, to determine the forms and methods of the organizational policy of republics’ mutual assistance during professional training for new buildings in Ukraine, the definition of success and controversy of this process